ARABIC ACQUISITION THROUGH FACEBOOK GROUP LEARNING - Mufidah, Nuril; Bin-Tahir, Saidna Zulfiqar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Facebook is a social media that is very popular with students in Indonesia. Thus, this study attempted to examine the increased of students’ Arabic acquisition through Facebook group learning. This research was quantitative research using quasi-experimental design. The sample of this study consists of two classes from the students of the Arabic language education department at UIN Maulana Malik Ibrahim. The instrument of this research was writing test. The results of this study indicated an increase of students’ Arabic acquisition so the researchers concluded that Facebook groups can improve the students’ ability to write in Arabic.